UNNA BOOT COMPRESSIVE THERAPY APPLIED TO VENOUS ULCERS - Martins Oliveira, Luiz Filipe (2023)
The objective of the research is to recognize the importance of the nurse's assistance to patients with venous ulcers using an unna boot. For development and analysis, the method used was the integrative review in the VHL and Scielo, databases of articles and theses published between 2014 and 2023. To construct the integrative review, 14 articles were selected based on titles and abstracts. It is concluded that nurses' assistance in caring for patients with venous ulcers, through compressive and topical techniques, has shown improvement in venous injuries, reduced pain, fewer recurrence rates, more comfort and quality of life.